SOLVING PROBLEMS OF STRESS STATE OF THICK NON-CIRCULAR CYLINDRO-ELLIPTICAL SHELLS WITH DIFFERENT INHOMOGENEOUS STRUCTURES ON THE BASIS OF ELASTICITY THEORY - Grigorenko О.Ya.; Rozhok, L.S.; Kruk, L.A.; Boreiko, N.P.; Kharytonova, L.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
The problem of the stress state of non-thin elliptical cylindrical shells made of continuous inhomogeneous material based on the spatial theory of the elasticity has been studied. The three-layer and the continuously nonhomogeneous materials of shell structures are considered. The shells are under normal internal pressure and have certain boundary conditions at the ends. The discrete-continuum approach was presented. The main concept of this approach is to reduce the original two-dimensional (three-dimensional) problems by using certain transformations to onedimensional boundary value problems, which are solved numerically on the basis of the discrete-orthogonalization method. The distribution of the value of the displacements and stresses fields depending on the shape of the cross section of the reference surface and the mechanical characteristics of the material was analysed. Continuously inhomogeneous shell material structure has a more existential effect on the distribution of the magnitude of normal displacements and stresses along the thickness compared to the three-layer material structure.